2016
DOI: 10.18632/oncotarget.13794
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism underlies atrazine toxicity in quails (Coturnix Coturnix coturnix): triggering ionic disorder via disruption of ATPases

Abstract: The widely used atrazine has been reported to exhibit extensive ecological hazards. Due to the biological accumulation, atrazine elicits widespread toxic effects on different organisms. However, true proof for the mechanism of atrazine-induced toxicity is lacking. To determine the potential mechanism by which atrazine exerted toxic effects, quails were treated with atrazine (0, 50, 250 and 500 mg/kg) by gavage administration for 45 days. Atrazine significantly increased the histological alterations and serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 77 publications
1
13
0
1
Order By: Relevance
“…Moreover, they exert important influence in regulating the transmembrane ionic balance to maintain proper function of the vasculature [35, 36]. The previous investigations demonstrated that high temperature inhibited the mitochondrial Ca 2+ -ATPase activity in broilers [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they exert important influence in regulating the transmembrane ionic balance to maintain proper function of the vasculature [35, 36]. The previous investigations demonstrated that high temperature inhibited the mitochondrial Ca 2+ -ATPase activity in broilers [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that once the ion balance is disrupted, cellular injury and disorders in cardiac function will occur [ 33 , 34 ]. The changes of cardiac ATPase activities and the transcription of its subunits could disturb the ionic homeostasis and finally induce heart injury in quails [ 35 , 36 ]. The heat stress caused a loss of ion homeostasis in marine crabs, which impaired the cardiac function [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted by HAYES [12] and others found that, when the growth of the African tree frog from larva to adult are exposed to the ATZ solution with the concentration of 0.1 μg/L, 20% of the young frogs will develop into hermaphrodites, which indicates that ATZ with a low concentration can feminize the male African tree frog. The team of Jia [13] indicated that ATZ can further cause heart and liver damage in quails by causing ion disturbances. Meanwhile, the study by Sanderson [14] and others discovered that ATZ can interfere with endocrine balance by increasing the activity of the CYP19 enzyme in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic ATR exposure results in high accumulative levels in multiple species, including frogs, fish, and rodents . Birds are one of the most important ecological pollution indicators due to their strong sensitivities to environmental pollutants . Overall, researches about the effect of ATR in birds might be particular significance to evaluations of the adverse effects of ATR in the environment.…”
Section: Introductionmentioning
confidence: 99%